Tourism research paradigms critical and emergent knowledges - Munar, Ana María; Jamal, Tazim (Emerald, 2016)
The theme of this book is the phenomenon of tourism and knowledge construction in tourism. Adopting a broad understanding of the paradigmatic field of tourism as the evolution and relationship between established and emergent schools of thought, this book explores the dynamics between tourism knowledge and the phenomenal world of tourism. It addresses contemporary epistemological debates and examines what constitutes tourism knowledge and how tourism knowledge is acquired. Issues examined in the chapters of this volume include: the nature and conceptualization of paradigms; the historical evolution of tourism knowledge production; embodiment, positionality and situated knowledges; paradigmatic proposals such as critical theory, feminism, humanism, cosmopolitanism, post-political theory and constructivism; a critical exploration of the power relations, contradictions and fragmentation in tourism research; ontologies and conceptualization of tourism and the tourist. This volume invites a critical evaluation and discussion of the anchorage of tourism as a knowledge domain and of tourism as science.
Keywords: Tourism -- Research.; elektronické knihy; electronic books